Istikhdām Wasīlah al-Kharīthah aż-Żihniyyah Bi Ṭarīqah at-Ta`allum at-Ta`āwunī Bi Uslūb Musābaqāt Tanāfus al-Farq (Team Game Tournament) Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Fahm al-Iḍāfah Wa aṣ-Ṣifah : استخدام وسيلة الخريطة الذهنية بطريقة التعلم التعاوني بأسلوب مسابقات تنافس الفرق لترقية قدرة الطلبة على فهم الإضافة والصفة - Nurmarini Nurmarini; Moch. Fajarul Falah (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
Mind Mapping can be described as a graphic design that provides the key to assisting brain abilities by utilizing most of the thinking skills using words, images, and colors. The title of this research is Using Mind Mapping Media with Cooperative Learning Methods Through Inter-group Competitions to Improve Students' Understanding of Al-Idhafah and As-Sifah (Experimental Research at Babun Najah Modern Islamic Boarding School in Banda Aceh). The method used is the True Experiment and the population is all students of Madrasah Tsanawiyah in the Babun Najah Modern Islamic Boarding School with a total of 492 students. The method used to determine the sample is a Cluster Random Sample from a population. The selected sample was students of class XI-Mia 2 as the control group and class Mia 4 as the experimental group. This study has two objectives, to find out how students respond to the application of Mind Maps with Cooperative Learning Methods through Inter-Group Competitions to Improve Students' Understanding of Al-Idhafah and As-Sifah and their effectiveness. The result of this research is the value of the t-count is greater than the t-table, which is 5.2> 2.05. This shows the effectiveness of the application of mind map media with cooperative learning methods in teaching Al-Idhafah and As-Sifah and has a good influence on second-grade students of MadrasahTsanawiyah at the Babun Najah Modern Islamic Boarding School.